Peran Dinas Perhubungan dalam Melakukan Pengawasan Terhadap Pelanggaran Jam Operasional Berdasarkan Peraturan Daerah Kabupaten Sukabumi Nomor 17 Tahun 2013 - Muhamad Ripki Ardiansyah; Agus Rasyid Chandra Wijaya (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This research aims to analyze the role of the Department of Transportation in supervising violations of the operational hours of container trucks and bottled drinking water (AMDK) based on the Regional Regulation of Sukabumi Regency Number 17 of 2013. This regulation is implemented as an effort to control the negative impacts of heavy vehicles operating outside the designated hours, including traffic congestion, road damage, and disruptions to the safety of other road users. The research method used is normative-empirical with a field study approach and conducting in-depth interviews with various stakeholders, such as the Department of Transportation, law enforcement officers, and transportation business operators. Research findings indicate that the Transportation Department of Sukabumi Regency has carried out its supervisory role through regular patrol activities, the placement of operational prohibition signs, and conducting socialization to drivers and transportation companies. However, there are still challenges in the implementation of supervision, such as limited human resources, lack of supporting facilities, and minimal coordination between different sectors.